Comparative Study of Hybrid Attribute Based Encryption for Cloud Computing System - Narmadhai, G; Bhanu, S. Vijay (International Journal of Computer Sciences and Engineering, 2025)
Due to reliability, there are million and millions of the uses and users of the cloud storages. So clouds are heavily developing field for various purposes. Many cloud hosts are providing services to different clients for their data storage. Due to disaster management cloud can be used as secured storage mechanism. For such cloud storages encryption is done many a ways for securing cloud data. The hybrid attribute based encryption i.e hybrid H-HABE is the method to encrypt the contents. This paper discusses the hybrid H-HABE encryption method for the cloud storages. The technique is also used to hide identity of the user that means the anonymous authentication can be implemented only by use of attributes. Our research work also analyses the importance of the data security in the cloud. Reason for choosing symmetric encryption algorithms are efficient to handle encryption and decryption for large amount of data, and effective speed of storing data and accessing the data in the cloud system. For implementation purpose here are considered the type of file as document file(doc), text file(txt) which can be enhance to sound file(.avi), video file, image file with different formats(BMP,JPG,GIFF,PNG).